Do aspirational role models inspire or backfire? Perceived similarity mediates the effect of role models on minority students' college choices. Issue 2 (2nd July 2020) - Allen, Evelyn C.; Collisson, Brian
ABSTRACT: Drawing from psychological theory, an aspirational role model within college marketing materials may cause prospective students to be willing to make similar enrollment and academic choices if the role model is perceived as similar to themselves. Therefore, we predicted that prospective, minority students exposed to a role model of the same, rather than different, ethnicity will be more willing to enroll in the same institution and make similar academic choices. Further, we predicted perceived similarity may mediate the effect of role model ethnicity on academic choices. To experimentally test our predictions, we presented 151 prospective, minority students (49% Black, 32.5% Hispanic, 18.5% Asian) with alumni profiles that varied in regard to ethnicity (same ethnicity, White) and accomplishment (modest, extreme). Prospective students then rated perceived similarity with the alumni and willingness to make similar academic choices. A series of analyses confirmed our predictions. Prospective, minority students were more willing to make similar choices when presented with a role model of the same, rather than different, ethnicity. As predicted, perceived similarity mediated the effect of role model ethnicity on academic choices. Interestingly, accomplishments of the alumni did not affect students' choices. Implications for recruiting students of color in higher education are discussed.